1987
DOI: 10.1093/jxb/38.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Catalase Activity and Post-anoxic Injury in Monocotyledonous Species

Abstract: Mont, L. S., Braendle, R. and Crawford, R. M. M. 1987. Catalase activity and post-anoxic injury in monocotyledonous species.-J. exp. Bot. 38: 233-246. Three anoxia-intolerant species, Glyceria maxima, Juncus effusus and Iris germanica (var. Quechei), and three anoxia-tolerant species Schoenoplectus lacustris, Acorus calamus and Iris pseuaacorus were chosen for investigation. Rhizomes of anoxia-intolerant species show increased catalase activities when returned to air after periods of prolonged anoxia. Levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
53
0
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 20 publications
3
53
0
2
Order By: Relevance
“…High post-anoxic levels of AA have been observed in potato tubers 5 h after re-aeration, following anoxic treatment for 24 to 72 h (Pfister-Sieber and Braendle, 1994). A 5-fold increase in AA has been observed 30 min after transfer to air for anoxic Glyceria maxima rhizomes (Monk et al, 1987a). The conversion of anaerobically accumulated ethanol to AA may account for these observations and may be one of the causes of post-anoxic injury (Studer and Braendle, 1988).…”
Section: Post-anoxic Aa Emissionmentioning
confidence: 99%
See 2 more Smart Citations
“…High post-anoxic levels of AA have been observed in potato tubers 5 h after re-aeration, following anoxic treatment for 24 to 72 h (Pfister-Sieber and Braendle, 1994). A 5-fold increase in AA has been observed 30 min after transfer to air for anoxic Glyceria maxima rhizomes (Monk et al, 1987a). The conversion of anaerobically accumulated ethanol to AA may account for these observations and may be one of the causes of post-anoxic injury (Studer and Braendle, 1988).…”
Section: Post-anoxic Aa Emissionmentioning
confidence: 99%
“…Two main pathways of ethanol oxidation, i.e. NAD+-dependent conversion of ethanol to AA catalyzed by the action of ADH, have been proposed (Monk et al, 1987a): (1) and H,O,-dependent catalase-controlled peroxidation…”
Section: Post-anoxic Aa Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monk et al ( 14) suggested that the reaction of acetaldehyde with proteins to give cross-linkages, carbinolamines, and Schifis bases may be responsible for cell death during the postanoxic phase. Acetaldehyde binds to proteins leading to the formation of both stable and unstable adducts (8); the latter, postulated to be Schiffs bases, can be stabilized in vitro ' Research supported by National Research Council of Italy, Special Project RAISA, Subproject 2,paper No.…”
mentioning
confidence: 99%
“…concentration (5,19) have been shown to influence catalase activity in mature plants. For example, Fair et al (5) demonstrated that catalase activity was suppressed when barley was grown in 1 to 5% CO2 and in 2% 02.…”
mentioning
confidence: 99%